A descriptive study on the concerns of the residents on the design of the bunk bed used in a selected university dormitory for males - Miranda, Carlo G.
The study intended to find out the concerns on the design of bunk beds used by the male residents in a university dormitory. Bunk bed design was evaluated based on the U.S. Consumer Product Safety Commission (1999) and the design reference standards by Panero and Zelnik (1979). Survey in questionnaire format was conducted using convenience sampling among 40 Filipino male residents of the selected University dormitory who have been using bunk beds for at least one semester. Descriptive format was utilized in data treatment for the bunk bed design. Results on bunk bed design concerns were obtained by getting the mode of each item. It was shown that the bunk bed design generally followed the guidelines, but with disparity on some design components. Bunk beds were frequently used during sleeping, daytime resting, reading books/studying, leisure time and using laptop. Pillows, blankets and hanging clothes, study table, electric fan and personal belongings were placed on and around the bunk beds. Bunk bed-related concerns of the top bunk users were the glare coming from the ceiling lamp, the need to go up and down frequently and the distance of the bed from the ceiling. For the bottom bunk users, the concerns were the movement of the user on the top bunk, possible blockage of lighting due to top bunk and the ladder connecting to the top bunk. Injury mechanisms commonly experienced included being bumped onto the ceiling, being bumped onto other bunk bed parts and hitting the posts of the bed. Common injuries sustained were contusions/bruises, abrasions and lacerations. The identified top causes of bunk-bed related injuries according to the respondents were absent-minded actions, internal anxiety and change of sleeping positions.